2010
DOI: 10.1002/pssa.200983717
|View full text |Cite
|
Sign up to set email alerts
|

Optical and transport properties of Ti‐doped In2O3 thin films prepared by electron beam physical vapour deposition

Abstract: Ti-doped In 2 O 3 (ITiO) thin films have been prepared by electron beam physical vapour deposition (EB-PVD). Their optical and electrical properties are studied for the obtained compositions. After oxygen annealing all samples show excellent optical transparence; additionally, maximum values for conductivity are obtained for samples with titanium contents near 6 at.%, with typical resistivity values of 4 Â 10 À5 V cm. Finally, the band-gap energy evolution is studied for the set of samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Highly dispersed Ti was observed in the elemental mapping analysis (Figure S2b–d). In the UV‐Vis analysis, the absorption peak position for Ti−In 2 O 3 was shifted towards lower wavenumber as compared to undoped In 2 O 3 due to the doping of Ti in In 2 O 3 (Figure S3) [31] . These results show that mixed oxide of In−TiO 2 and Ti−In 2 O 3 were formed and the dopant was dispersed in the parent oxide without formation of agglomerated particles.…”
Section: Resultsmentioning
confidence: 85%
“…Highly dispersed Ti was observed in the elemental mapping analysis (Figure S2b–d). In the UV‐Vis analysis, the absorption peak position for Ti−In 2 O 3 was shifted towards lower wavenumber as compared to undoped In 2 O 3 due to the doping of Ti in In 2 O 3 (Figure S3) [31] . These results show that mixed oxide of In−TiO 2 and Ti−In 2 O 3 were formed and the dopant was dispersed in the parent oxide without formation of agglomerated particles.…”
Section: Resultsmentioning
confidence: 85%
“…The Ti-content in the films prepared by this EB-PVD preparation technique are considerably lower compared to the values in the starting pellet . Therefore, the starting pellets were made with very high Ti-content (up to nearly 95 at %) and, consequently, the evaluation of the Ti content of each studied film was necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Indium molybdenum, indium tungsten, and indium titanium oxides (IMO, IWO, and ITiO, respectively) thin films present transparent conductive properties with low electrical resistivity and high mobility. , Specifically, ITiO has been recently reported to have an excellent electronic mobility for Ti content below 5 at % . This system has been prepared by different methods: pulsed laser deposition, magnetic null discharge sputter source or by sputtering from ceramic targets and recently by electron beam physical vapor deposition (EB-PVD). In all of them, conductive samples are obtained for Ti contents lower than 20 at %.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been reported that thin films with very high mobility (80-130 cm 2 V À1 s À1 ) can be obtained by either thermal reactive evaporation or pulsed laser deposition, 11,12 and films with low resistivity (4 Â 10 À5 X-cm) by can be obtained by electron beam physical vapor deposition. 13 On thecontrary, Ga, Aldoped zinc oxide (GAZO) has been regarded as one of the most competitive TCOs due to the advantages of its abundance in nature, nontoxicity, stability in hydrogen plasma, high transmittance in the visible range, and lower resistivity. It has been studied as an alternative material for transparent conductive ITO thin films.…”
Section: Introductionmentioning
confidence: 99%